Promoting bidirectional extracellular electron transfer of Shewanella oneidensis MR‐1 for hexavalent chromium reduction via elevating intracellular cAMP level - Cheng, Zhou‐Hua; Xiong, Jia‐Rui; Min, Di; Cheng, Lei; Liu, Dong‐Feng; Li, Wen‐Wei; Jin, Fan; Yang, Min; Yu, Han‐Qing (Biotechnology and bioengineering, 2020)
The bioreduction capacity of Cr(VI) by Shewanella is mainly governed by its bidirectional extracellular electron transfer (EET). However, the low bidirectional EET efficiency restricts its wider applications in remediation of the environments contaminated by Cr(VI). Cyclic adenosine 3′,5′‐monophosphate (cAMP) commonly exists in Shewanella strains and cAMP–cyclic adenosine 3′,5′‐monophosphate receptor protein (CRP) system regulates multiple bidirectional EET‐related pathways. This inspires us to strengthen the bidirectional EET through elevating the intracellular cAMP level in Shewanella strains. In this study, an exogenous gene encoding adenylate cyclase from the soil bacterium Beggiatoa sp. PS is functionally expressed in Shewanella oneidensis MR‐1 (the strain MR‐1/pbPAC) and a MR‐1 mutant lacking all endogenous adenylate cyclase encoding genes (the strain Δca/pbPAC). The engineered strains exhibit the enhanced bidirectional EET capacities in microbial electrochemical systems compared with their counterparts. Meanwhile, a three times more rapid reduction rate of Cr(VI) is achieved by the strain MR‐1/pbPAC than the control in batch experiments. Furthermore, a higher Cr(VI) reduction efficiency is also achieved by the strain MR‐1/pbPAC in the Cr(VI)‐reducing biocathode experiments. Such a bidirectional enhancement is attributed to the improved production of cAMP–CRP complex, which upregulates the expression levels of the genes encoding the c‐type cytochromes and flavins synthetic pathways. Specially, this strategy could be used as a broad‐spectrum approach for the other Shewanella strains. Our results demonstrate that elevating the intracellular cAMP levels could be an efficient strategy to enhance the bidirectional EET of Shewanella strains and improve their pollutant transformation capacity. A novel strategy is developed to improve the bidirectional extracellular electron transfer of Shewanella strains in this study. Cheng and coworkers provide the convincing evidences that elevating the intracellular cAMP levels could be used as a simple but efficient strategy to enhance the bidirectional EET of Shewanella strains and improve their pollutant degradation capacity. This strategy could be used as a broad‐spectrum enhancement method for other dissimilatory metal‐reducing bacteria.